Strategies and Tactics in Gaining Public Opinion - Simonyan, Armine (Armenian Folia Anglistika, 2009)
One of the contemporary spheres of modern linguistics is the study of political discourse. For a politician, language is a weapon to win the favours of public at large. The article aims to reveal how American politicians use English to receive the support of the nation. The research is conducted on the debates between the US presidential candidates in 2008 – Hillary Clinton and Barak Obama. The reason for the choice is obvious. Both candidates, as members of the same party, seem to have a lot in common. Both belong to the same party, hence, they should have an audience committed to the same democratic principles whereas, the differences are more than obvious. It is the first time in the history of the United States that the post of the US president has two main candidates that are so different – a woman and a coloured man. The article includes research on the tactics and strategies applied by both the candidates.